Theoretical Data Extraction for Tooth Surface Measurement of Straight Bevel Gear based on Solid Modeling - Li Tianxing; Xu Jinghui; Yang Jingzhao; Zhou Junxiang; Wang Guofeng; Xing Chunrong (Jixie chuandong)
Aiming at the tooth surface error measurement results distortion of straight bevel gear which consisted of the of modification error and machining error based on gear measuring center,a method which is proposed to obtain the theoretical coordinates for tooth surface measurement based on the solid modeling.According to the design of the gear structure,the origin of the coordinate system and datum plane can be determined by installation distance,then the rotating projection line model can be established based on the calculated mesh nodes coordinates,a series of points are converted to the tooth surface,combined with UG Open programming technology,the attribute analysis of the points on the tooth surface can be extracted,then the coordinates and unit vector of the tooth surface measurement points can be obtained,which provides a new way for the acquisition of the tooth surface error measurement based on gear measuring center.